2008
DOI: 10.1044/0161-1461(2008/032)
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minimal Hearing Loss on Children’s Ability to Multitask in Quiet and in Noise

Abstract: Purpose The purpose of the present study was to examine the effect of minimal hearing loss on children’s ability to perform simultaneous tasks in quiet and in noise. Methods Ten children with minimal hearing loss (HL) and eleven children with normal hearing (NH) participated. Both groups ranged in age from 8 to 12 years. The children categorized common words (primary task) while completing dot-to-dot games (secondary task) in quiet as well as in noise presented at 0 and +6 dB signal-to-noise ratios (SNR). It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 23 publications
3
59
0
3
Order By: Relevance
“…In addition, the findings suggest that paradigm sensitivity may not have been solely responsible for previously reported nonsignificant findings; the simple paradigm in the present study was modeled after the one used by Hicks and Tharpe (2002) and was found to be sensitive to the effects of noise. There are several alternative possible reasons why effects of noise on listening effort were found in the present study but not in others (e.g., Hicks & Tharpe, 2002;McFadden & Pittman, 2008). These possible explanations include SNR, task engagement, and participant age.…”
Section: Effects Of Background Noisementioning
confidence: 65%
See 2 more Smart Citations
“…In addition, the findings suggest that paradigm sensitivity may not have been solely responsible for previously reported nonsignificant findings; the simple paradigm in the present study was modeled after the one used by Hicks and Tharpe (2002) and was found to be sensitive to the effects of noise. There are several alternative possible reasons why effects of noise on listening effort were found in the present study but not in others (e.g., Hicks & Tharpe, 2002;McFadden & Pittman, 2008). These possible explanations include SNR, task engagement, and participant age.…”
Section: Effects Of Background Noisementioning
confidence: 65%
“…In the present study, word recognition performance was significantly degraded by implementing poor SNRs (0 to −2 dB), whereas Hicks and Tharpe (2002) and McFadden and Pittman (2008) used more positive SNRs (+2 to +10dB and 0 to +6 dB, respectively). Indeed, consistent with the present results, Howard et al (2010) reported significant increases in listening effort comparing secondary task performance in quiet and at a −4 dB SNR.…”
Section: Effects Of Background Noisementioning
confidence: 91%
See 1 more Smart Citation
“…For example, suggested that the effects of language delays in children with mild to moderate hearing loss might be mediated through by a hearing loss-related compromise of working memory. In support of this hypothesis, others have reported that children with UMHL expend more cognitive resources when listening or multitasking compared with TH children (Dokovic et al 2014;McFadden and Pittman 2008). If more cognitive capacity being directed toward other tasks, such as listening, social skills development is likely to be affected.…”
Section: How Social Skills Relate To Language Developmentmentioning
confidence: 52%
“…Research on children with UMHL has mainly focused on language and academic skills and conveys mixed findings: whereas some studies report outcomes for children with UMHL that are comparable to those of TH children (Fitzpatrick et al 2015;Niedzielski et al 2006;Wake et al 2006), others report difficulties among children with UMHL McFadden and Pittman 2008). A recent review identified many areas in which UMHL children may suffer compared with their TH peers; however, there is great variability within the group, and risk factors have not yet been sufficiently investigated .…”
Section: Outcomes In Children With Unilateral and Mild Bilateral Hearmentioning
confidence: 99%